The Elephant in the Room: A Place for Wikipedia in Higher Education? - Brox, Hilde (Nordlit, 2012)
The article departs from a pilot survey among Norwegian teacher students that maps their usage, skills and attitudes in relation to the web based encyclopedia Wikipedia. The survey shows that the students are heavy users of Wikipedia content yet show a low level of knowledge as to how content is constructed or the ways in which Wikipedia differs from traditional, paper-based encyclopedias. The students also express little interest in parttaking in creating content or maintaining the site. The second part of the article argues that a way to remedy both lack of knowledge and interest among students is to bring Wikipedia actively into the classrooms and enable students to take part in creating and maintaining Wikipedia content. This way, Wikipedia may serve as an effective tool with which to address and enhance a range of central 21st century skills.